2001
DOI: 10.1055/s-2001-15320
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Manifestations of Primary Colorectal Lymphoma

Abstract: Based on the analysis of colonoscopic records, we have proposed three main types of primary colorectal lymphoma. An unusually high proportion of T-cell lineage lymphomas was noted, but as the number of cases was low, further study is still needed for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 11 publications
(13 reference statements)
0
34
0
3
Order By: Relevance
“…In the study conducted in 4 continents with 1378 patients, Anderson et al [17] have shown that the distribution of NHL subtypes differs in various geographical areas and suggested that this could be a reflection of differences in etiological factors or the host response to these factors. Unlike western countries, frequency of T cell lymphoma in the East is reported to be 17.9%-42% [18,19] . Primary colorectal lymphoma differs from its gastric counterpart.…”
Section: Definition Types and Etiologymentioning
confidence: 99%
“…In the study conducted in 4 continents with 1378 patients, Anderson et al [17] have shown that the distribution of NHL subtypes differs in various geographical areas and suggested that this could be a reflection of differences in etiological factors or the host response to these factors. Unlike western countries, frequency of T cell lymphoma in the East is reported to be 17.9%-42% [18,19] . Primary colorectal lymphoma differs from its gastric counterpart.…”
Section: Definition Types and Etiologymentioning
confidence: 99%
“…In the West, almost all primary colorectal lymphomas have been reported to be of the B-cell lineage (6,7). However, some cases of primary colorectal T-cell lymphoma have been reported from the East (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…6 T hücreli lenfomaların prognozlarının daha kötü olduğu bildirilmektedir. 8 Tanıda kolonoskopi ve bilgisayarlı tomografi sık olarak kullanılır. Bilgisayarlı tomografi ile lezyonun lokalizasyonu ve görüntülenmesi yapılır.…”
Section: Discussionunclassified